A three dimensional transmitting boundary formulated in Cartesian co-ordinate system for the dynamics of non-axisymmetric foundations. - Kim, Jae Kwan
A three dimensional transmitting boundary is formulated in the Cartesian co-ordinate system. It is developed for the dynamic soil structure interaction problems of arbitrary shape foundations in laterally heterogeneous strata overlying rigid bedrock. Dynamics of a rectangular rigid surface foundation on a homogeneous stratum is analysed by a hybrid approach in which the finite region including foundation is modelled by the conventional finite element method and the surrounding infinite region by the newly developed transmitting boundary. To demonstrate its strength, the present method is applied to a rectangular foundation in a horizontally heterogeneous ground consisting of two distinct regions divided by and welded along a vertical plane.
Keywords: Transmitting boundary; Hyperelement; Soil structure interaction; Rectangular foundation; Heterogeneous ground